Africa's Great Moderation - Sebastian Krantz (Kiel Institute for the World Economy (IfW Kiel), 2022)
Over the past 30 years (1990-2019), African economies have experienced remarkable improvements in real macroeconomic conditions, characterized by higher and more stable real per-capita growth rates, and lower and more stable inflation, which deserves to be called a "Great African Moderation". This paper documents the persistent decline in macroeconomic volatility at the aggregate and sectoral levels and seeks to provide some explanations. Sectoral analysis shows a particularly strong reduction of growth volatility in agriculture, followed by services. On the expenditure side, private consumption and investment growth have stabilized considerably. Analysis of a broad range of explanatory factors yields that only a small fraction of the Africa Moderation can be explained by structural change, or changes in major structural characteristics such as institutions, trade intensity, and diversification, natural resource dependence, or conflict incidence. Rather, this paper brings forth evidence to suggest that changes in the external environment (terms of trade, external debt), improved macroeconomic policy frameworks (exchange rate management, fiscal rules), and 'softer' structural improvements such as the deepening of the financial sector and increases in human capital, were important towards reducing volatility on the continent.
Keywords: O11; E30; E60; 330; macoeconomic stability; structural resilience; growth; inflation; volatility; structural change; economic structure; institutions; macroeconomic policy